(ax+by)mũ2-(ay+bx)mũ2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Trả lời
1, \(3\left(x-1\right)^2-5x\left(x-6\right)=3\)
\(\Leftrightarrow3\left(x^2-2x+1\right)-5x^2+30x=3\)
\(\Leftrightarrow3x^2-6x+3-5x^2+30x=3\)
\(\Leftrightarrow-2x^2+24x+3=3\)
\(\Leftrightarrow-2x^2+24x=0\)
\(\Leftrightarrow-2x\left(x-12\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}-2x=0\\x-12=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=12\end{cases}}}\)
Vậy x = 0; x = 12
2, \(\left(x-5\right)^2-36=0\)
\(\Leftrightarrow\left(x-5\right)^2-6^2=0\)
\(\Leftrightarrow\left(x-5-6\right)\left(x-5+6\right)=0\)
\(\Leftrightarrow\left(x-11\right)\left(x+1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-11=0\\x+1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=11\\x=-1\end{cases}}}\)
Vậy x = 11; x = - 1
3, \(\left(x-1\right)^2-4x+3=0\)
\(\Leftrightarrow x^2-2x+1-4x+3=0\)
\(\Leftrightarrow x^2-6x+4=0\)
\(\Leftrightarrow x^2-2.x.3+9-5=0\)
\(\Leftrightarrow\left(x-3\right)^2-5=0\)
\(\Leftrightarrow\left(x-3\right)^2=5\)
\(\Leftrightarrow\orbr{\begin{cases}x-3=\sqrt{5}\\x-3=-\sqrt{5}\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\sqrt{5}+3\\x=-\sqrt{5}+3\end{cases}}\)
Vậy \(x=\sqrt{5}+3;x=-\sqrt{5}+3\)
4, \(\left(2x-1\right)^2+\left(x+3\right)^2-5\left(x+7\right)\left(x-7\right)=0\)
\(\Leftrightarrow4x^2-4x+1+x^2+6x+9-5\left(x^2-49\right)=0\)
\(\Leftrightarrow5x^2+2x+10-5x^2+245=0\)
\(\Leftrightarrow2x+255=0\)
\(\Leftrightarrow2x=-255\)
\(\Leftrightarrow x=-\frac{255}{2}\)
Vậy x = - 255/2
5, \(\left(x+2\right)^2-x^2+8=0\)
\(\Leftrightarrow x^2+4x+4-x^2+8=0\)
\(\Leftrightarrow4x+12=0\)
\(\Leftrightarrow4x=-12\)
\(\Leftrightarrow x=-3\)
Vậy x = - 3
![](https://rs.olm.vn/images/avt/0.png?1311)